Introduction to the foundations and ways of defending free competition (Revista do Tribunal Regional Federal da 3ª Região, 2020)
This study addresses the foundations and means by which free competition is protected in Brazil. The analysis seeks to present the reasons why, in a dialog between Law and Economics, the normative protection of the possibility of competition is justified and to identify the instruments by which the various branches of Law protect the performance of free enterprise. Throughout the study, it is revealed how the protection of competition is carried out not only by CADE, but also by the Judiciary in various areas of law, and can even result from a provocation by the injured party themselves.
Keywords: competition; economic power; consumer; efficiency